COMMON FIXEDPOINTTHEOREM IN COMPLETE INTUITIONISTICFUZZY METRIC SPACE - et al., Krishnaveni S (International Journal of Advanced Science and Technology, 2019)
In this paper we have introduced rational type contractive conditions in a complete intuitionistic fuzzy metric space. Using this, we proved some common fixed-point theorem in a complete intuitionistic fuzzy metric space.